Flood-prone settlements and mosquito habitat risk: An integrated field survey and spatial mapping - Zul Janwar; Zulkarnain; Nururrahmah Hammado; St Aisyah Humaerah (EcoVision: Journal of Environmental Solutions, 2026)
Background: Flood-prone areas present significant public health challenges, particularly in urbanized regions where inadequate drainage systems and water stagnation create ideal breeding grounds for disease vectors such as mosquitoes. This study investigates the relationship between flood risks and mosquito habitat proliferation in Gowa, South Sulawesi, Indonesia. Methods: By combining a comprehensive field survey with Geographic Information System (GIS) spatial mapping, the study aimed to identify environmental and infrastructural factors contributing to mosquito breeding, particularly Aedes aegypti, the primary vector for dengue and Zika virus. Findings: The results revealed that areas with poorly managed drainage systems and stagnant water were high-risk zones for mosquito breeding, correlating with increased mosquito densities and higher disease transmission potential. The study also found that rapid urbanization, combined with insufficient waste management, further exacerbates the risk by providing numerous breeding sites for mosquitoes. The findings support global observations that similar challenges in other tropical regions, including Brazil and Indonesia, contribute to the spread of mosquito-borne diseases. Conclusion: This research highlights the critical role of environmental infrastructure in controlling vector-borne diseases and emphasizes the need for improved urban planning, integrated vector control strategies—including better drainage infrastructure, community education, and regular sanitation practices—to reduce mosquito breeding sites. Overall, it provides valuable insights for local authorities and public health organizations, offering a framework for targeted interventions in flood-prone areas. Novelty/Originality of this article: The novelty of this study lies in combining GIS spatial mapping with field surveys to directly link flood-prone urban infrastructure and environmental factors to mosquito habitat proliferation, providing a framework for targeted, location-specific public health interventions.